A Double-Bed Adsorptive Heat Transformer for Upgrading Ambient Heat: Design and First Tests - Mikhail Tokarev (Energies, 2019)
A full scale lab prototype of an adsorptive heat transformer (AHT), consisting of two adsorbers, an evaporator, and a condenser, was designed and tested in subsequent cycles of heat upgrading. The composite LiCl/SiO2 was used as an adsorbent with methanol as an adsorbtive substance under boundary temperatures of TL/TM/TH = −30/20/30 °C. Preliminary experiments demonstrated the feasibility of the tested AHT in continuous heat generation, with specific power output of 520 W/kg over 1−1.5 h steady-state cycling. The formal and experimental thermal efficiency of the tested rig were found to be 0.5 and 0.44, respectively. Although the low potential heat to be upgraded was available for free from a natural source, the electric efficiency of the prototype was found to be as high as 4.4, which demonstrates the promising potential of the “heat from cold” concept. Recommendations for further improvements are also outlined and discussed in this paper.